Magnetic moment measurements in the semi-magic nuclei 94Ru and 95Rh after recoil implantation into iron and nickel - Jungclaus, Andrea; Kast, D.; Lieb, K.P.; Lingk, C.; Teich, C.; Iordanov, O.; Härtlein, T.; Schwalm, Dirk; Johnstone, I.P.; Schwengner, R. (The European physical journal. A, Hadrons and nuclei, 1999)
The magnetic moments of the 12+ and 11− yrast states in 94Ru and of the 25/2−, 29/2+, and 35/2+ levels in 95Rh have been measured via the IMPAD technique. The nuclei were produced in the reaction 58Ni +40Ca and recoil-implanted into polarized Ni and Fe hosts. The g-factors were deduced from the measured time-integral Larmor precessions. The comparison between the experimental results and large-scale shell model calculations suggests that the 12+ and 11− states in 94Ru and the 25/2− level in 95Rh are pure proton states whereas the 29/2+ and 35/2+ states in 95Rh contain a neutron excitation across the N=50 shell gap. This interpretation supports the conclusion drawn from recent lifetime measurements.
Im Titel sind "94" und "95" als Hochzahlen dargestellt
Gesehen am 30.11.2020